Infection with Helicobacter pylori may predispose to atherosclerosis: role of inflammation and thickening of intima-media of carotid arteries - Aramouni, Karl; Assaf, Roland K.; Azar, Maria; Jabbour, Karen; Shaito, Abdullah; Sahebkar, Amirhossein; Eid, Assaad A.; Rizzo, Manfredi; Eid, Ali H. (Frontiers in Pharmacology, 2023)
Atherosclerosis is a major instigator of cardiovascular disease (CVD) and a main cause of global morbidity and mortality. The high prevalence of CVD calls for urgent attention to possible preventive measures in order to curb its incidence. Traditional risk factors of atherosclerosis, like age, smoking, diabetes mellitus, dyslipidemia, hypertension and chronic inflammation, are under extensive investigation. However, these only account for around 50% of the etiology of atherosclerosis, mandating a search for different or overlooked risk factors. In this regard, chronic infections, by Helicobacter pylori for instance, are a primary candidate. H. pylori colonizes the gut and contributes to several gastrointestinal diseases, but, recently, the potential involvement of this bacterium in extra-gastric diseases including CVD has been under the spotlight. Indeed, H. pylori infection appears to stimulate foam cell formation as well as chronic immune responses that could upregulate key inflammatory mediators including cytokines, C-reactive protein, and lipoproteins.These factors are involved in the thickening of intima-media of carotid arteries (CIMT), a hallmark of atherosclerosis. Interestingly, H. pylori infection was found to increase (CIMT), which along with other evidence, could implicate H. pylori in the pathogenesis of atherosclerosis. Nevertheless, the involvement of H. pylori in CVD and atherosclerosis remains controversial as several studies report no connection between H. pylori and atherosclerosis. This review examines and critically discusses the evidence that argues for a potential role of this bacterium in atherogenesis. However, additional